Inovasi produk TOGA Immunomodulator dan budidayanya - Darini Kurniawati; Nurul Hidayah; Siti Malahayati (Indonesia Berdaya, 2023)
The Covid-19 pandemic has an impact on partners and they want to innovate businesses that are needed by the community, namely herbal products that can increase endurance but are more durable and can be stored. Methods with education and practice of making traditional herbal instant powder preparations by conventional means of crystallization by heating and adding granulated sugar. Jamu powder is packaged and labeled as partners. Business licensing assistance has been carried out and has sold it directly or digital marketing with Instagram and WhatsApp promotional posters. Raw material efforts are assisted by cultivating the immunomodulator TOGA in the partner's yard. Evaluation of education by conducting a pre-test and post-test with the results obtained an increase in the category of good knowledge level by 58%. Evaluation of production that sells a lot is red ginger instant powder, while TOGA cultivation thrives waiting for harvest age. Abstrak: Pandemi Covid-19 berdampak terhadap mitra dan menginginkan berinovasi usaha yang diperlukan  masyarakat yaitu produk herbal yang bisa meningkatkan daya tahan tubuh tapi lebih awet dan bisa disimpan. Metode dengan edukasi dan praktek pembuatan sediaan serbuk instan jamu tradisional dengan cara konvensional kristalisasi melalui pemanasan dan penambahan gula pasir. Serbuk jamu dikemas dan diberi label mitra. Pendampingan perijinan usaha sudah dilakukan dan sudah menjualnya secara langsung maupun marketing digital dengan poster propmosi  Instagram dan whattshap. Upaya bahan baku dibantu dengan budidaya TOGA imunomodulator di lahan pekrangan mitra. Evaluasi edukasi dengan melakukan pre-test dan post-test dengan hasil diperoleh kenaikan kategori tingkat pengetahuan baik sebesar 58%. Evaluasi produksi yang banyak terjual yaitu serbuk instan jahe merah, sedangkan budidaya TOGA tumbuh subur menunggu usia panen.